2019
DOI: 10.3390/ani9090701
|View full text |Cite
|
Sign up to set email alerts
|

Denatonium Benzoate-Induces Oxidative Stress in the Heart and Kidney of Chinese Fast Yellow Chickens by Regulating Apoptosis, Autophagy, Antioxidative Activities and Bitter Taste Receptor Gene Expressions

Abstract: Simple SummaryDenatonium benzoate is a strong bitter taste receptor agonist, extensively used for its activation of different cell pathways. Taste signals have been associated to food recognition and avoidance, and bitter taste provokes an aversive reaction and is assumed to protect chickens from consuming poisons and harmful toxic substances. The results of the study revealed that dietary supplementation with medium and high doses of denatonium benzoate damaged the epithelial cells of the heart and kidneys by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…DB is a bitter substance and known agonist of bitter taste receptors (T2Rs) in different cells [20]. T2Rs are G protein-coupled receptors playing a primary role as central warning signals to induce aversion toward noxious or harmful substances.…”
Section: Discussionmentioning
confidence: 99%
“…DB is a bitter substance and known agonist of bitter taste receptors (T2Rs) in different cells [20]. T2Rs are G protein-coupled receptors playing a primary role as central warning signals to induce aversion toward noxious or harmful substances.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained tissue sections were collected on glass slides, deparaffinized and stained by hematoxylin and eosin stain for histopathological examination. Five sections of testis from each of three different doses were observed for the histological changes in the seminiferous tubules as the previous method reported [28,29,30,31]. (Total of 30 sections were observed from each mouse).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, research has revealed that denatonium benzoate, an agonist of TAS2R1, 2, 7, and α-gustducin, at low dose (5 mg/kg) and short period of treatment (i.e. 7 days) causes a decrease in the expression of apoptosis and autophagy-related genes—caspase (Casp) 2, Casp3, Casp7, Casp9, Bcl-2l1 (B cell lymphoma 2 like 1), Mcl (mantle cell lymphoma), Bid (BH3-interacting domain death agonist), and Noxa (NADPH oxidase activator), along with increased expression of antioxidant enzymes or mediators such as glutathione peroxidase 1 (Gpx1), catalase (CAT), superoxide dismutase 1 (SOD1) and calpain-1 in whole heart tissues of experimental animals (Hamdard et al 2019b ). However, at higher doses and chronic treatment with denatonium benzoate, Hamdard et al ( 2019a , b ) demonstrated increased expression of the apoptosis and autophagy-related genes, suggesting that TAS2R activation may be beneficial at low doses and acute treatment period (Hamdard et al 2019b ).…”
Section: Bitter Taste Receptors Of the Heart And Their Signal Transdu...mentioning
confidence: 99%
“…Flufenamic acid is a TAS2R14 agonist (Meyerhof et al 2010 ) and a member of the anthranilic acid derivative class of nonsteroidal anti-inflammatory drugs (Chi et al 2011 ). Though it is not exactly clear whether the anti-inflammatory effect of flufenamic acid is due to its stimulatory action on TAS2R, available data suggest that this TAS2R14 agonist can modulate the expression of COX-2 gene via interaction with the NF-κB pathway (vide infra) or NADH oxidase signalling (Hamdard et al 2019b ). Indeed, activation of TAS2R1, 8, 10, 13, 14, and 38 by the human gut microbiota-derived quorum-sensing signal molecule, 3-oxo-C12:2-HSL in LPS- and IFNγ-stimulated RAW264.7 macrophages reportedly resulted in decreased expression of the proinflammatory cytokines IL-1β and TNFα via modulation of the NF-κB, Janus kinases/Signal transducer and activator of transcription (JAK/STAT) and TNF signalling pathways (Coquant et al 2022 ).…”
Section: Bitter Taste Receptors Of the Heart And Their Signal Transdu...mentioning
confidence: 99%
See 1 more Smart Citation